2013
DOI: 10.1093/carcin/bgt168
|View full text |Cite
|
Sign up to set email alerts
|

An insulin-like growth factor-II intronic variant affects local DNA conformation and ovarian cancer survival

Abstract: Insulin-like growth factor-II (IGF-II) may be a prognostic marker in ovarian cancer, and its intronic single nucleotide polymorphism (SNP) rs4320932 has been associated with risk of the disease. We determined whether rs4320932 is associated with IGF-II expression and patient survival in ovarian cancer, and explored whether the SNP variation affects DNA conformation both in the absence of and presence of carboplatin. IGF-II genotype (rs4320932) and phenotype were analyzed in 212 primary invasive epithelial ovar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Unfortunately, subject to the limitation of relatively small sample size, we were not able to explore this issue. In addition, although the functions of intronic SNPs are still obscure, studies have indicated that they can affect the secondary structure of either local DNA or RNA, thereby regulating gene expression 39 40…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, subject to the limitation of relatively small sample size, we were not able to explore this issue. In addition, although the functions of intronic SNPs are still obscure, studies have indicated that they can affect the secondary structure of either local DNA or RNA, thereby regulating gene expression 39 40…”
Section: Discussionmentioning
confidence: 99%
“…Another significant molecule, excision repair cross-complementation 1 (ERCC1), which encodes an ERCC1 protein, is involved in the NER pathway, eliminating significant DNA damage generated through environmental agents including toxic compounds or ultraviolet (10). Genetic variations, such as single nucleotide polymorphism (SNP) may exchange amino acids or modify DNA conformations, which is related to cancer risk or human disorders (11,12). Single nucleotide polymorphism molecular analysis could facilitate prognosis, diagnosis, and remedy of human disorders (13).…”
Section: Introductionmentioning
confidence: 99%
“…Single nucleotide polymorphism (SNP) is a single nucleotide change in a DNA sequence, which may change DNA or RNA conformations (Lu et al, 2012(Lu et al, , 2013 or lead to amino acid substitution (Roberts et al, 2011), thereby resulting in corresponding phenotypes. SNPs may cause human diseases and/or contribute to the risk of diseases, and their identification may help us discover new ways to diagnose, treat, and prevent human diseases (Ulrich et al, 2003).…”
Section: Introductionmentioning
confidence: 99%